Rancang Bangun Sistem Penyewaan Sarana dan Prasarana Olahraga Berbasis Web pada Dinas Pendidikan, Kepemudaan dan Olahraga Kabupaten Kudus - Syahrul Mahendra Saputra; Ahmad Jazuli; Rina Fiati (KOLONI, 2026)
The Kudus Regency Education and Sports Office is responsible for managing the local government's sports facilities and infrastructure, which can also be utilized by the public through a rental system. In addition to being used for government activities, these facilities are rented to companies, organizations, and the general public as a source of increasing regional revenue. Currently, the rental process is still carried out manually, starting from checking availability, submitting applications, to direct payments, which are quite time-consuming and inefficient. This problem has prompted the need to develop a web-based rental information system that can simplify the service process. This system was built using the Waterfall software development method with the Laravel Livewire framework and supported by system design using flowcharts, use case diagrams, activity diagrams, and class diagrams. The implementation of this system is expected to improve ease of service access, accelerate the rental process, and increase the effectiveness of sports facility management. Thus, the utilization of local government sports facilities can be more optimal and contribute to increasing local revenue and economic growth in Kudus Regency. The development of this system is also expected to increase transparency, data accuracy, and minimize errors in the administrative process of sports facility rentals within the Kudus Regency Education and Sports Office. This system is integrated and effective in a modern digital manner. Keywords: information system, facility rental, Laravel Livewire, Waterfall, website.